From street art to murals: what have we lost? - Abarca, Javier (SAUC - Street Art and Urban Creativity (repository), 2016)
The mural festivals that have become common all over the world in the last five years are often called street art festivals, and the murals produced in those festivals are often referred to as street art. This use of the term creates confusion, since there are clear and fundamental differences between the smaller, unsanctioned works we used to call street art in the past decade and the huge institutional murals of today. The aim of this text is to try and identify the differences between these two practices.